Elucidating Spatially-Resolved Changes in Host Signaling During Plasmodium Liver-Stage Infection - Glennon, Elizabeth K. K.; Tongogara, Tinotenda; Primavera, Veronica I.; Reeder, Sophia M.; Wei, Ling; Kaushansky, Alexis (Frontiers in Cellular and Infection Microbiology, 2022)
Upon transmission to the human host, Plasmodium sporozoites exit the skin, are taken up by the blood stream, and then travel to the liver where they infect and significantly modify a single hepatocyte. Low infection rates within the liver have made proteomic studies of infected hepatocytes challenging, particularly in vivo, and existing studies have been largely unable to consider how protein and phosphoprotein differences are altered at different spatial locations within the heterogeneous liver. Using digital spatial profiling, we characterized changes in host signaling during Plasmodium yoelii infection in vivo without disrupting the liver tissue. Moreover, we measured alterations in protein expression around infected hepatocytes and identified a subset of CD163+ Kupffer cells that migrate towards infected cells during infection. These data offer the first insight into the heterogeneous microenvironment that surrounds the infected hepatocyte and provide insights into how the parasite may alter its milieu to influence its survival and modulate immunity.